The combination of covalent and ionic exchange immobilizations enables the coimmobilization on vinyl sulfone activated supports and the reuse of the most stable immobilized enzyme - Arana Peña, Sara; Carballares, Diego; Morellon Sterling, Roberto; Rocha Martin, Javier; Fernandez Lafuente, Roberto (International Journal of Biological Macromolecules, 2021)
The coimmobilization of lipases from Rhizomucor miehei (RML) and Candida antarctica (CALB) has been intended using agarose beads activated with divinyl sulfone. CALB could be immobilized on this support, while RML was not. However, RML was ionically exchanged on this support blocked with ethylendiamine. Therefore, both enzymes could be coimmobilized on the same particle, CALB covalently using the vinyl sulfone groups, and RML via anionic exchange on the aminated blocked support. However, immobilized RML was far less stable than immobilized CALB. To avoid the discarding of CALB (that maintained 90% of the initial activity after RML inactivation), a strategy was developed. Inactivated RML was desorbed from the support using ammonium sulfate and 1% Triton X-100 at pH 7.0. That way, 5 cycles of RML thermal inactivation, discharge of the inactivated enzyme and re-immobilization of a fresh sample of RML could be performed. In the last cycle, immobilized CALB activity was still over 90% of the initial one. Thus, the strategy permits that enzymes can be coimmobilized on vinyl sulfone supports even if one of them cannot be immobilized on it, and also permits the reuse of the most stable enzyme (if it is irreversibly attached to the support).